Descriptive study of onychomycosis in a hospital in São Paulo - Ribeiro, Clarissa Santos De Carvalho; Zaitz, Clarisse; Framil, Valéria Maria De Souza; Ottoboni, Thaíssa Santos De Carvalho; Tonoli, Melissa Santos De Carvalho [UNESP]; Ribeiro, Renata Pinheiro (Sociedade Brasileira de Microbiologia, 2015)
Onychomychosis, a nail fungus infection is the most frequent nail ailment, constituting about half of all nail disorders. It can be caused by dermatophytes, non-dermatophytes, yeasts and Prothoteca spp. Methods include 5407 samples of patients with suspected onychomycosis, studied from January 2002 to December 2006, by direct mycological examination and fungi culture. The diagnosis of onychomycosis was confirmed in samples from 3822 direct mycological and/or culture positive. The diagnosis was established by culture for fungi. Among the 1.428 identified agents, the dermatophytes were responsible for 68.6% (N = 980) of cases, followed by yeasts with 27.6% (N = 394), non-dermatophytes fungi with 2.2% (N = 31), Prothoteca spp with 0.1% (N = 2), and associations with 1.5% (N = 22). Females were more affected, with 66% (N = 2527) of cases, and the most affected age group ranged from 31 to 60 years of age (median 47 years). Fungal microbiota is often changed in the world, both quantitatively and qualitatively, and is affected by several environmental factors. Thus, the periodic review of the composition of this microbiota is important to evaluate the epidemiology and thus proportion a better therapeutic response.
Keywords: Onychomycosis; Dermatophytes; Yeasts; Non-dermatophytes fungi; Prothoteca spp